Ciliados no plâncton da planície de inundação do alto rio Paraná (MS/PR - Brasil) : estrutura e dinâmica da comunidade. - Pauleto, Gustavo Mayer (2009)
This study aimed to investigate the main patterns of temporal and spatial composition, species richness, abundance and community structure of planktonic ciliates, still little studied in the Upper Paraná River Floodplain. Furthermore, we set out to identify the responses of these organisms to environmental variations, both spatial and temporal, in this complex ecosystem. So, samples were taken monthly, between March 2007 and February 2008, at three depths of Guaraná Lake, in addition to sampling in twelve environments, lotic, lentic and semi-lentic, representative of the whole system, during two different hydrological periods (March and September 2007). This work was divided into three chapters: the first was entitled Changes in spatial and temporal composition of species of planktonic ciliates in a lentic environment of the floodplain in Brazil , in which we observed patterns of variation in the composition of species of ciliates apparently related to the disruptive effect of flood pulses on environmental stability. In the second chapter, "Spatial and temporal changes in community structure of ciliates in a pond in the floodplain , it was found that the Guaraná Lake is characterized by a typical lacustrine ciliate community during the limnofase, going to receive a most significant influence of the communities from the river and benthic and littoral regions, in the rainy season. The third chapter, Species richness, abundance and community structure of planktonic ciliates in the Upper Paraná River Floodplain showed the effect of flooding across the floodplain-river system, determining significant seasonal changes of ciliate communities, and demonstrated that in this period there is a homogenization of the attributes of these communities among the different environments of this ecosystem. In general, the results of this study suggest a more effective participation of ciliates in traditional grazing food web, contrasting to the paradigm that protozoa are essentially involved in microbial detritivores food web, and show the flood pulse as the main factor structuring the planktonic ciliates communities of the Upper Paraná River Floodplain.